Etching yields and surface reactions of amorphous carbon by fluorocarbon ion irradiation. (31st May 2017) - Karahashi, Kazuhiro; Li, Hu; Yamada, Kentaro; Ito, Tomoko; Numazawa, Satoshi; Machida, Ken; Ishikawa, Kiyoshi; Hamaguchi, Satoshi
Abstract: Etching yields of amorphous carbon (a-C) have been determined for Ar +, Ne +, F +, CF +, and CF3 + ion irradiation as functions of ion incident energy in the range from 300 to 2, 000 eV. Amorphous carbon is often used as a hard mask material for reactive ion etching (RIE) of Si-based materials and its durability against chemically reactive etching is of primary importance. In this study, experiments on the ion-beam etching of a-C films were performed with a mass-selected ion beam system, which irradiated a sample surface with a single ion species at a specified incident energy under ultra high vacuum conditions. It is found that the etching yield of a-C can be strongly enhanced by the chemical effects of fluorine (F) contained in the incident ions over the corresponding physical sputtering yield. The yield data also show that the etching yield of a-C by fluorocarbon ions depends more sensitively on the amount of fluorine supplied to the surface than those of Si-based materials such as Si, SiO2, and Si3 N4 . Therefore, to minimize the erosion of a-C mask structures in an etching process for Si-based materials by fluorocarbon plasmas, one must optimize the fluorine content in the etching gas while maintaining sufficiently large etching rates for Si-based materials to be etched.